Child-Witnessed Domestic Violence and its Adverse Effects on Brain Development: A Call for Societal Self-Examination and Awareness - Tsavoussis, Areti; Stawicki, Stanislaw P. A.; Stoicea, Nicoleta; Papadimos, Thomas J. (Frontiers in Public Health, 2014)
There is substantial evidence indicating that children who witness domestic violence have psychosocial maladaptation that is associated with demonstrable changes in the anatomic and physiological make up of their central nervous system. Individuals with these changes do not function well in society and present communities with serious medical, sociological, and economic dilemmas. In this focused perspective we discuss the psychosocially induced biological alterations (midbrain, cerebral cortex, limbic system, corpus callosum, cerebellum, and the hypothalamic, pituitary, and adrenal axis) that are related to maladaptation (especially post-traumatic stress disorder) in the context of child-witnessed domestic violence, and provide evidence for these physical alterations to the brain. Herein we hope to stimulate the necessary political discourse to encourage legal systems around the world to make the act of domestic violence in the presence of a child, including a first time act, a stand-alone felony.